High‐Fidelity, Narcissistic Self‐Sorting in the Synthesis of Organometallic Assemblies from Poly‐NHC Ligands - Sinha, Narayan; Tan, Tristan T. Y.; Peris, Eduardo; Hahn, F. Ekkehardt (Angewandte Chemie International Edition, 2017)
Highly selective, narcissistic self‐sorting has been observed in the one‐pot synthesis of three organometallic molecular cylinders of type [M3{L‐(NHC)3}2](PF6)3 (M=Ag+, Au+; L=1,3,5‐benzene, triphenylamine, or 1,3,5‐triphenylbenzene) from L‐(NHC)3 and silver(I) or gold(I) ions. The molecular cylinders contain only one type of tris‐NHC ligand with no crossover products detectable. Transmetalation of the tris‐NHC ligands from Ag+ to Au+ in a one‐pot reaction with retention of the supramolecular structures is also demonstrated. High‐fidelity self‐sorting was also observed in the one‐pot reaction of benzene‐bridged tris‐NHC and tetrakis‐NHC ligands with Ag2O. This study for the first time extends narcissistic self‐sorting in metal–ligand interactions from Werner‐type complexes to organometallic derivatives. Perfect sorting! Unique narcissistic self‐sorting has been observed in the one‐pot reaction of three different trigonal trisimidazolium salts with Ag2O. Only three cylinder‐like trinuclear complexes each bearing two identical tris‐NHC ligands were obtained from this reaction. Self‐sorting was also observed in the subsequent transmetalation of the tris‐NHC ligands from the three silver(I) complexes to give three gold(I) complexes.